FORMULASI TEPUNG PELAPIS SAVORY CHIPS IKAN NIKE (Awaous melanocephalus) - Nikmawatisusanti Yusuf; Sri Purwaningsih; Wini Trilaksani (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2012)
Fish savory chips is one type of fish-based snacks with a crunchy texture and crispy. Crispiness is a typical characteristic of the chips product. Utilization of nike fish (Awaous melanocephallus) as raw material for a snack is one of fishery products diversification, as well as an alternative of a healthy snack with high nutritional content. The purpose of this study was to determine the formula of coating powder of nike fish savory chips which highly nutritions. Three formula of powder with ratio of 2:1 were used (A = rice flour and tapioca; B = tapioca flour and wheat; C = wheat flour and rice) and added with natrium bicarbonate (baking soda) as crisp makers with different concentrations (1%, 1.5%, and 2%), and spices consisting of salt, pepper, garlic, and coriander. The analyses performed included crispiness and organoleptic. The formula chosen was determined by Bayes test. The results of crispiness measurement showed that the formula A (rice flour and tapioca flour (2:1)) had the best crispy value, compared to B (flour & tapioca flour (2:1)), and C (wheat andrice flour (2:1)). Formula that used of 1.5% crisp maker had a better crispness value than 1% and 2%. Bayes test results showed that formula A with a concentration of 1.5% crisp maker was the best formula for nike fish savory chips.Key words: Awaous melanocephalus, formulation, crispiness, savory chips